Oscillatory Properties of the Solutions of First Order Linear Neutral Differential Equations with “Maxima” - Malacka, Zuzana (Communications - Scientific letters of the University of Zilina, 2013)
In this paper we consider a neutral differential equation with "maxima" of the form [x(t) + p(t)x(σ(t))] + q(t) max x(s) = 0 We obtained sufficient conditions for oscillation of all the solutions when t→∞.